Pengembangan Media Kartu Domino Materi Persamaan dan Pertidaksamaan Linear Satu Variabel (PLSV) Kelas VII SMP - Nurhidayati, Dwi; Khabibah, Siti; Sa’adah, Nihayatus (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
One of the goals of using learning media is to improve the quality of student learning and make the learning process more interesting. Domino card learning media is one of the game innovations that can be used in the classroom. This study aims to describe the level of feasibility of domino card learning media on the material of Linear Equations and Inequality One Variables by adapting the ADDIE development model. The data collection technique used is a questionnaire. Questionnaires are divided into two types, namely validation questionnaires and student response questionnaires. The validation stage of learning media products is carried out by material experts, media experts, and learning practitioners. While the student response questionnaire with small group test subjects by three students and field trials by all students of class VII B. The validation results from material experts obtained an average score of 3.17 with a percentage of 63.3% and the criteria